Continuous flow method for the simultaneous determination of phosphate/arsenate based on their different kinetic characteristics - Borgnino Bianchi, Laura Carolina (2011)
This paper proposes a new automated spectrophotometric method for the simultaneous determination of phosphate and arsenate without pre-treatment, which is faster, simpler, less expensive and hazardous than other well-known methods used with water samples. Such method is based on the different kinetic characteristics of complex formation of phosphate and arsenate with ammonium molybdate. A flow system was used in order to achieve good mixing and to provide precise time control. All the measurements were performed at the isosbestic point wavelength (885 nm). Chemical variables were optimized by factorial design (ammonium molybdate 0.015 mol L -1, potassium antimony tartrate 1 × 10 -4 mol L -1, and sulphuric acid 0.7 mol L -1). An appropriate linear range for both analytes (0.50-8.00 μmol L -1), good inter-day reproducibility (4.9% [P] and 3.3% [P + As]) and a sample throughput of 6 h -1 were obtained. The detection limits are 0.4 μmol L -1 P and 0.19 μmol L -1 [P + As] (3.3 Sy/x). The method was validated. © 2011 Elsevier B.V. All rights reserved.